Royalists and Dwarfs Take to the Streets. Culture of Resistance in the Activities of Movements of Czech Children and Orange Alternative - Balcerzak, Małgorzata (Poznańskie Studia Slawistyczne, 2014)
This article is an attempt to compare two contestation models, that occurred in the activities of new social movements formed in the 80s of the twentieth century in Czechoslovakia and Poland (Czech Children and Orange Alternative). Both movements are the examples of the changes taking place in the process to form of political and social opposition to the communist regime. The article describes the relationship between political commitment and understanding of the aesthetic function (influence of surrealism) in the culture of opposition.